Embedding gamification elements in Distributed Pair Programming (DPP): a conceptual framework / Mahfudzah Othman ... [et al.] - Othman, Mahfudzah; Paidi, Zulfikri; Abu Bakar, Noor Azilah Abu Bakar; Muhd Zain, Nurzaid (UiTM Cawangan Perlis, 2016)
This paper discusses a conceptual model of a web system for distributed pair programming (DPP) that involves the use of gamification elements as the new feature of the system. DPP is one of the efforts that support pair programming over geographically distributed environment. Pairs from dispersed locations can communicate with each other to code or completing tasks via the Internet. The proposed model involved the development of a web system that facilitates DPP with the use of web-based applications and web 2.0 tools. Nevertheless, in order to make the web system more fun and interactive, gamification elements are embedded in the proposed model. Suitable game mechanics based on gamification Octalysis Framework are selected that focused on the development and achievement of each pair in the DPP web system. The aim of the proposed model is not only to encourage the use of the gamified DPP web system but also to improve learners' experiences in learning programming that is stress free and more interactive.